2011
DOI: 10.1001/archoto.2010.240
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin A for Treatment of Sialorrhea in Children

Abstract: Ultrasonographically guided botulinum toxin A injections into the salivary glands are safe and efficacious in the management of sialorrhea in children with neurologic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 27 publications
4
43
0
2
Order By: Relevance
“…It is considered to have efficacy rates ranging from 89% to 95% when injected in both submandibular and parotid glands. BoNTs injections improve symptoms effectively but temporarily; patients usually require more than one injection for drooling control . The effect by injection varies from 6 weeks to 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered to have efficacy rates ranging from 89% to 95% when injected in both submandibular and parotid glands. BoNTs injections improve symptoms effectively but temporarily; patients usually require more than one injection for drooling control . The effect by injection varies from 6 weeks to 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Minor complication rates reported in the literature range from 0% 9,10 to 11.1% 11 for submandibular gland injection and 0% 9,10,12,13 to 18.7% 14 for submandibular and parotid gland injection. No major complications were reported for submandibular gland injection.…”
mentioning
confidence: 98%
“…9 Considering the increasing use of BoNT for drooling, studies to identify possible risk factors for adverse effects on oral motor functions before treatment are urgently needed. 10 Post-intervention assessments showed that adverse effects on oral motor functions with a potential negative effect on swallowing occurred from 0% [11][12][13] up to 17.8% 6 of the cases after submandibular gland injections, and up to 33% 14 of the cases after combined submandibular/parotid gland injections. To date no major complications were identified after submandibular injections.…”
mentioning
confidence: 99%